Occupational Medicine Status of Kashan Industries by Weighted Checklist to Analytical Hierarchy Process Mthod in 2019 - Abbas BAHRAMI; Reihaneh GHORBANI-POUR; Habibollah RAHIMI; Mohammad hosein MEMARI-NASHALJI (Shahid Sadoughi University of Medical Sciences, 2021)
Introduction: Workers' health status is one of the main factors affecting industry productivity. Therefore, effective employee periodic examinations are important not only for the benefit of industries and for improving the health of workers but also for the health of the community. Methods: This descriptive study was done in98 on 60 cases of industries of Kashan that they had occupational health expert. The tools were occupational medicine items Ministry of Health checklists after weight by Analytical Hierarchy Process. Data were analyzed by SPSS 21 software. Results: Assessing the occupational medicine status of Kashan industries with this checklist showed that according to cut-off point 70, 18 industries (30% of the industries) scored poorly. Results of linear regression analysis showed that there is a significant relationship between work experience of occupational health experts with occupational health status of industry (P <0.05). Conclusion: Due to the evaluation and prioritization of 10 items of occupational medicine status in Kashan industries, it is suggested that the relevant authorities in their health interventions consider these priorities